Plane and space in pattern design - Kirsti Salo-Mattila (Techne Series: Research in Sloyd Education and Craft Science A, 2014)
In garment design, flat pattern design is central to form giving. In designing, the three-dimensional form is developed in two dimensions. Interaction between the two-dimensional presentation and three-dimensional reality is characteristic of the process. Despite its essential role in the teaching and learning of pattern design, the process has received only a limited interest in didactic studies. Internationally, most of the studies are American, and they have concentrated on the effects of spatial ability. The present article enquires how students in the textile teacher program of a Finnish university experienced the flat pattern design process and its difficulties, and what kind of processes were actually used. The results of the conducted survey indicate that studies in clothing design and construction had only a minor effect on how the students evaluated the difficulty of various pattern design tasks on the advanced level as compared with the introductory level. The possibility that this is due to crafts in the curriculum of  the Finnish comprehensive school is discussed. As to the processes of pattern design, the survey found that on the advanced level, when the students were free to choose among various alternatives, more than half of the processes were different from each other. Half of the processes included a mix of 2D and 3D methods, and two thirds of the total were iterative in nature. Improvement of design and ease allowances were the main reasons for iteration. After the basics, a flexible approach to the pattern design process appears to be advantageous for students' development in the subject.